Religious Experience in Muslim Philanthropy: An Epistemological and Ethical Discourse - Munifatussaidah, Asma; Kuswanjono, Arqom (Universitas Muhammadiyah Ponorogo, 2025)
Muslim philanthropy is a practical form of the religious experience of Muslim communities that mediates between individual belief in amaliyah activities and collective ownership to build an Islamic environment. This research explains the representation of religious experience in the context of Muslim philanthropy from the perspective of Islamization, a perspective of returning to Islamic values in behavior. Using the literature method, this research describes Islamic epistemology and theology shape the understanding and depiction of religious experience in the discourse and practice of philanthropy among Muslims. The research also explains the epistemic of Muslim philanthropy and its implications for religious and ethical contexts. By views from Muslim scholars, religious texts, and contemporary discourses on philanthropy, explain the worldview of Islam through religious experience in philanthropy or giving behavior.